Reduksi Kadar Besi Dalam Air Sumur di Lingkungan Universitas Muhammadiyah Surakarta dengan Filter - Pawarti, Hesti; Citradewi, Lia Intan; Fadhilla, Aulia Tassya; Suhendi, Andi (Universitas Muhammadiyah Surakarta, 2018)
Iron was silvery white, clay, and can be formed. it was usually obtained as hematite in nature. Iron was a chemical element that could be found in almost all places on the face of the earth, in all parts of the geological layer, and all bodies of water. In surface water, Fe was rarely found more than 1 mg / L, but in the water, Fe content could be much higher. When it accumulated in the body, iron could cause health problems, such as skin irritation, respiratory problems, and cause cancer in a long time. This study aims to determine the reduction of iron content in well water at the Universitas Muhammadiyah Surakarta (UMS) using the Spectrophotometry method with phenanthroline reagents. The samples were taken as many as five points in three different regions, namely Tanuragan (near the river), Menco and Nilasari (dense settlements), and Gonilan (near the rice fields) showed positive results containing iron with the highest levels in the sample without filtering at 9,478 ppm. These levels decreased after filtration using four filters, namely filters made of carbon, cotton, foam, carbon three layers in each sample. The iron content reduction was best to use cotton filters with 100% reduction in percent.